Comparison of whole-body muscle imaging findings between GNE myopathy and other young adult-onset hereditary myopathies - Pattira Boonsri; Suppakorn Yamutai; Pramot Tanutit; Jirakit Sattayapornpipat; Chariyawan Charalsawadi; Prut Koonalintip; Pornchai Sathirapanya; Suwanna Setthawatcharawanich; Rattana Leelawattana; Pat Korathanakhun (PLoS ONE, 2026)
Objectives Previous muscle imaging studies of GNE myopathy are limited to the lower extremities. This study aimed to use whole-body MRI to differentiate between GNE myopathy and other young adult-onset hereditary myopathies. Materials and methods This retrospective cohort study recruited patients with GNE myopathy or young adult-onset hereditary with limb girdle weakness pattern followed up in a single-center neuromuscular clinical registry between 2019 and 2023. Fatty tissue replacement was evaluated using a 5-point scale using T1-weighted images (T1WI) and proton-density fat fractions (PDFF) from mDIXON Quant images. Inflammation was evaluated using short tau inversion recovery imaging. The distribution and severity of muscle involvement in GNE myopathy were visualized using heat maps, and the parameters were tested for significance. Results Of 103 patients, five with GNE myopathy and 10 with young adult-onset hereditary myopathy were recruited. Prominent fatty tissue replacement was seen in specific muscles with subtle active inflammation in GNE myopathy. The comparison of fatty tissue replacement between GNE and other young adult-onset hereditary myopathies exhibited the classic quadriceps sparing pattern in GNE myopathy group. Beyond these findings, latissimus dorsi showed the significantly lower fatty tissue replacement in the GNE group (median [IQR] of T1WI grade 1 [0, 1] vs. 3 [1, 3.4], p = 0.04) and mean (± S.D.) of PDFF in mDIXON Quant (19.0 ± 9.7 vs. 42.6 ± 22.7, p = 0.04). Conclusion The latissimus dorsi sparing out of proportion to periscapular weakness would be a novel differentiative feature of GNE myopathy.